2020
DOI: 10.1038/s41598-020-75685-3
|View full text |Cite
|
Sign up to set email alerts
|

A non-classical route of efficient plant uptake verified with fluorescent nanoparticles and root adhesion forces investigated using AFM

Abstract: Classical plant uptake is limited to hydrophilic or water-dispersible material. Therefore, in order to test the uptake behaviour of hydrophobic particles, here, we tested the fate of hydrophobic particles (oleylamine coated Cu2-xSe NPs (CS@OA)) in comparison to hydrophilic particles (chitosan-coated Cu2-xSe NPs (CS@CH)) by treatment on the plant roots. Surprisingly, hydrophobic CS@OA NPs have been found to be ~ 1.3 times more efficient than hydrophilic CS@CH NPs in tomato plant root penetration. An atomic forc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The plant's mechanism of nanoparticle adsorption and absorption to enhance the efficacy of the entrapped agrochemicals is a popular topic of interest (Avellan et al 2021;Grillo et al 2021a). Previous studies have shown that these mechanisms are influenced by the particle's size (Cui et al 2008), charge (Hu et al 2020), and hydrophobicity (Sharma et al 2020;Zhang et al 2021). Research focusing on the foliar applications of pesticide entrapped nanoparticles is often conducted as these plant tissues are frequently exposed to pests and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The plant's mechanism of nanoparticle adsorption and absorption to enhance the efficacy of the entrapped agrochemicals is a popular topic of interest (Avellan et al 2021;Grillo et al 2021a). Previous studies have shown that these mechanisms are influenced by the particle's size (Cui et al 2008), charge (Hu et al 2020), and hydrophobicity (Sharma et al 2020;Zhang et al 2021). Research focusing on the foliar applications of pesticide entrapped nanoparticles is often conducted as these plant tissues are frequently exposed to pests and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the absence of individual rGO sheets or Cu 2– x Se NCs confirms the successful synthesis of rGO-Cu 2– x Se composite. The HR-TEM performed on Cu 2– x Se NCs and rGO-Cu 2– x Se shows lattice fringes having a d -spacing value of 0.33 nm, which corresponds to the (111) plane of Cu 2– x Se NCs (inset in Figure C,D). Here, the average particle size found to be decrease from 15 to 9 nm as compared to our previous work, after changing the copper to selenourea ratio. This size reduction is important for the diseases control here as inverse proportion of the Cu particles size with the antimicrobial property has been observed before, and here it is expected to contribute for the combination antifungal efficiency with captan.…”
Section: Resultsmentioning
confidence: 49%
“…While hydrophilic NPs should not be able to directly cross the cuticle, recent work has described a higher root uptake of NP presenting a hydrophobic surface (Sharma et al, 2020). This suggests that the cuticle layers might not be as impenetrable as what was previously hypothesized in the literature and that uptake depends on the NP coating, corona formation, and resulting surface properties.…”
Section: Reaching the Rhizoplane And Entering The Rootmentioning
confidence: 84%